Noise-induced Intermittent Oscillation Death in a Synergetic Model - Jaimes-Reátegui, R.; Magallón-García, D. A.; Gallegos, A.; Huerta-Cuellar, G.; HGarcL, J; Pisarchik, A. N. (Discontinuity, Nonlinearity, and Complexity, 2026)
We study noise-induced intermittency in a synergetic model of two coupled oscillators with asymmetric nonlinear coupling. This model was previously used to simulate visual perception of ambiguous images. We show that additive noise induces preference for one of the coexisting unstable steady states. When the noise intensity exceeds a certain threshold value, the oscillations of one of the coupled subsystems are interrupted during some time intervals, resulting in intermittent oscillation death, while another subsystem exhibits noisy oscillations in the vicinity of an unstable fixed point.